Socio-economic affecting child malnutrition in Tacloban City. - Miranda, Aubrey; Uyvico, Dexter Ax G. (Aubrey Miranda [and] Dexter Ax G. Uyvico, 2010)
This study aimed to determine the socio-economic factors which contribute most to child malnutrition in selected 5 barangays in Tacloban City namely: 48-A, 80, 83-B, 90, and 92.